De lagarta a borboleta: as competências em ação dos Gestores Técnicos-Administrativos das Instituições Federais de Ensino Superior do Nordeste Brasileiro - Pereira, Aline Lucena Costa (2010)
The overall objective of this study is to analyze the competencies in action of the technical and administrative managers of federal institutions of higher education (IFES) in northeastern Brazil and the following are specific objectives: a) identify the competencies in action of managers of IFES in their professional practice, b) set the dimensions of the competencies of the technical and administrative managers and c) measure, as perceived by managers, the domain level and the level of encouragement from IFES regarding managerial competencies identified. The theoretical framework was divided into five parts: (i) competencies: a construct preparation, (ii) managerial competencies, (iii) the historical evolution of IFES, (iv) public context: the current scenario of human resource management and (v) public manager's role: challenges and opportunities. The research configures itself as qualitative and quantitative nature, of the exploratory and descriptive type, being held in two stages: a qualitative through focus groups and a quantitative survey using an electronic source of data collection. The sets of qualitative research were three federal universities: Federal University of Paraiba UFPB, Federal University of Pernambuco UFPE and the Federal University of Rio Grande do Norte UFRN. The qualitative phase included 21 public managers in the areas of human resources, finance, accounting, and security that work in those institutions. In the data collect the focus group technique was used in order to uncover the perceptions of managers, identifying the managerial competencies present in their professional practices. The interviews were transcribed and the information handled by the analysis of qualitative data. The quantitative stage was performed in 14 IFES located in northeastern Brazil, using a survey. The results allowed enlarge the understanding of management competencies in the public scope, enabling to identify four dimensions present in the managerial competencies in the design of these managers in the public sector: Competencies of Institutional Development Management, Competencies of Behavioral Management, Competencies of Organizational Environment Management and Competencies of Political management, as well as measure the domain and encouragement level perceived in each competence.